2019
DOI: 10.3390/en12040706
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Operation Regulation of a Coupled High–Low Energy Flue Gas Waste Heat Recovery System Based on Exhaust Gas Temperature Control

Abstract: Controlling the exhaust gas temperature (EGT) of coal–fired boilers at a reasonable value is beneficial to ensuring unit efficiency and preventing acid corrosion and fouling of tail heating surfaces in power plants. To obtain the operation regulation of coupled high–low energy flue gas waste heat recovery system (CWHRS) under a given EGT, experimental equipment was designed and built. Experiments were carried out to maintain the exhaust gas temperature under different flue gas flow, flue gas temperature and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The FWCRS has been applied to a 1000 MW ultra-supercritical double reheat coal-fired unit [34]. The technical process of the system is displayed in Figure 2 [35]. Up to 30% of high-temperature flue gas flows through an HPE and an LPE in sequence to heat boiler feed water and condensed water respectively, and the bypass flue gas valve is used to adjust the flue gas flow.…”
Section: Description Of Fwcrsmentioning
confidence: 99%
“…The FWCRS has been applied to a 1000 MW ultra-supercritical double reheat coal-fired unit [34]. The technical process of the system is displayed in Figure 2 [35]. Up to 30% of high-temperature flue gas flows through an HPE and an LPE in sequence to heat boiler feed water and condensed water respectively, and the bypass flue gas valve is used to adjust the flue gas flow.…”
Section: Description Of Fwcrsmentioning
confidence: 99%
“…Furthermore, Xu W et al have explored the efficacy of employing high-temperature boiler feedwater technology for recuperating medium-low temperature flue gas waste heat. Their research focused on optimizing thermal efficiency while managing exhaust temperatures and addressing the issue of low-temperature corrosion in the tail flue [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that exhaust gas energy is affected not only by the outlet flue gas temperature of the boiler side but also by the comprehensive solution of steam/water side exhaust gas. Liu et al 12 obtained the operating rules of High− Low Energy FGWHRS at an exhaust gas temperature of 85 °C. The results showed that the bypass flue gas flow rate plays a decisive role in improving the heat recovery efficiency, while the circulating water flow rate has little influence on the heat recovery efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that exhaust gas energy is affected not only by the outlet flue gas temperature of the boiler side but also by the comprehensive solution of steam/water side exhaust gas. Liu et al . obtained the operating rules of High–Low Energy FGWHRS at an exhaust gas temperature of 85 °C.…”
Section: Introductionmentioning
confidence: 99%